108k views
3 votes
-x - 5y - 5z = 2
4x - 5y + 4z = 19
x + 5y – z = -20

User Gravity
by
5.3k points

2 Answers

7 votes

Answer:

4x - 5y + 4z = 19

x + 5y - z = -20

5x + 3z = -1

-x - 5y - 5z = 2

x + 5y - z = -20

-6z = -18

z = 3

5x + 3(3) = -1

5x + 9 = -1

5x = -10

x = -2

-2 + 5y - 3 = -20

5y - 5 = -20

5y = -15

y = -3

x - 2, y = -3, z = 3

Explanation:

User Hypno
by
5.6k points
5 votes

Answer:

Explanation:

-x - 5y - 5z = 2

x + 5y - z = -20

-6z = -18

z = 3

4x - 5y + 12 = 19

x + 5y - 3 = -20

4x - 5y = 7

x + 5y = -17

5x = -10

x = -2

2 - 5y - 15 = 2

-5y - 13 = 2

-5y = 15

y = -3

{x = -2, y = -3, z = 3}

User Natsfan
by
5.4k points